Moving North: Intra-Racial Conflicts, White Resistance, And Radicalism of New Negroes in Harlem and Chicago - Muhammad Beni Saputra (Universitas Islam Negeri Sunan Kalijaga, 2022)
In the early twentieth century there was an essential period in the history of the United States called the Great Migration, during which a large number of Blacks from the southern states of America and the islands in the Caribbean moved to northern cities of the country. These black people migrated simply because 'of the impact of the war on the labor market' which 'stopped the flow of European immigrants' and of the fact that jobs in northern cities had a better pay than those in the South. From many destinations, Harlem and Chicago were among the most favored ones. This essay aims to examine the motivations and experiences of New Negroes in Harlem and Chicago as these two cities drew much attention to Blacks in the Southern cities of America as well as in the Caribbean. This essay argues that the influx of Blacks to Harlem and Chicago created intra-racial conflicts within black communities and resistance from white people. Yet all the disputes and problems faced by New Negroes in Harlem and Chicago inspired them to fight actively by organizing themselves in order to find workable solutions.